A Decision Analysis of Observation vs Immediate Reintervention for Asymptomatic Residual Fragments Less than 4 mm Following Ureteroscopic Lithotripsy. Issue 5 (September 2019) - Ursiny, Michal; Yaghoubian, Alan; Humphreys, Mitchell R.; Brotherhood, Hilary; Chew, Benjamin H.; Monga, Manoj; Krambeck, Amy E.; Charchenko, Cameron; Wang, An Qi; Sur, Roger L.; Miller, Nicole L.; Marien, Tracy; et al.
Abstract: Introduction: We performed a decision analysis model of the cost-effectiveness of observation vs intervention for asymptomatic residual fragments less than 4 mm in diameter following ureteroscopic holmium laser lithotripsy. Methods: Outcomes data from a retrospective analysis evaluating the natural history, complications and reintervention rates of asymptomatic residual stone fragments performed by the EDGE (Endourology Disease Group for Excellence) Research Consortium were used. A decision analysis model was constructed to compare the cost-effectiveness of initial observation of residual fragments to immediate intervention. Cost of observation included emergency room visits, hospitalizations and reinterventions. The cost analysis model extended to 3 years to account for delayed reintervention rates for fragments less than 4 mm. Costs of emergency department visits, readmissions and reinterventions were calculated based on published figures from the literature. Results: Decision analysis modeling demonstrated that when comparing initial observation to immediate reintervention, the cost was 2, 183 vs 4, 424. The difference in cost was largely driven by the fact that over 3 years, approximately 55% of all patients remained asymptomatic and did not incur additional costs. This represents an approximate annual per patient savings of 747, and 2, 241 over 3 years when observation is selected over immediate reintervention. Conclusions: Our decision analysis model demonstrates superior cost-effectiveness for observation over immediate reintervention for asymptomatic residual stones less than 4 mm following ureteroscopic lithotripsy. Based on these findings careful stratification and selection of patients may enable surgeons to improve cost-effectiveness of managing small, asymptomatic residual fragments following ureteroscopic lithotripsy.